Deconfinement and chiral restoration in nonlocal SU(3) chiral quark models - Carlomagno, Juan Pablo (2013)
We study the features of nonlocal SU(3) chiral quark models with wave function renormalization. Model parameters are determined from meson phenomenology, considering different nonlocal form factor shapes. In this context we analyze the characteristics of the deconfinement and chiral restoration transitions at finite temperature, introducing the couplings of fermions to the Polyakov loop. We analyze the results obtained for various thermodynamical quantities considering different Polyakov loop potentials and nonlocal form factors, in comparison with data obtained from lattice QCD calculations.